The contribution of social cognition in predicting social participation following moderate and severe TBI in youth. Issue 9 (21st October 2019) - Sirois, K.; Tousignant, B.; Boucher, N.; Achim, A.M.; Beauchamp, M. H.; Bedell, G.; Massicotte, E.; Vera-Estay, E.; Jackson, P. L.
ABSTRACT: Youth with moderate or severe traumatic brain injury (TBI) are at risk for reduced social participation after the injury, and the contribution of social cognition to these changes in functioning has been little studied. This study aimed to examine social participation and to measure the contribution of social and non-social cognitive functions to social participation impairment in youth (ages 12–21) who sustained moderate or severe TBI. Youth with TBI ( n  = 23) were compared to typically developing (TD) controls on self- and parent-rated social participation questionnaires. Direct testing of social cognition (mentalising, social knowledge, emotion recognition) and higher order cognitive abilities (intellectual abilities, attention and executive functions) was also conducted. Significant differences were found between the TBI participants and TD controls on social participation measures. Mentalising and problem-solving abilities revealed to be significant correlates of social participation as reported by youth with brain-injury and their parents. Overall, these results corroborate previous findings by showing that social participation is significantly reduced after TBI, and further shows that mentalising, which is not always considered during rehabilitation, is an important contributing factor. In addition to executive function measures, social cognition should therefore be systematically included in assessment following youth TBI for intervention and prevention purposes.